The Effect of The Combination of Bioslurry and Spacing on The Growth and Yield of Shallots (Allium Ascalonicum L.) Varieties of Bima Brebes - Tety Suciaty; Achmad Faqih; Ayu Retno Wati; Mubarik Izul Fitri; Rifki Nopendi; Selamet Riyadi (Pusat Publikasi Nusantara, 2023)
The study aims to find out: (1) The effect of the combination of bioslurry and spacing of shallots (Allium Ascalonicum L.) (2) The effect of the combination of bioslurry concentration and the best planting distance on the ha sil of onion plants (Allium Ascalonicum L.). (3) Correlation between growth components and yield of onion plants (Allium Ascalonicum L.). The research was conducted in Karangwangun Village, Babakan District, Cirebon Regency - West Java. The research was conducted from August to December 2022. The experimental method used is using the experimental method with Group Random Design (RAK), the treatment consists of two factors that are repeated 3 times. The first factor is bioslurry with concentrate of 5% or 50 ml/lt, 10% or 100 ml/lt, 15% or 150 ml/lt. While the second factor is the planting distance which consists of three levels, namely planting distances of 20 cm x 10 cm, 20 cm x 15 cm, 20 cm x 20 cm. The main observation data were processed using statistical tests, fingerprint analysis, and further test analysis of the Scott-Knott group. To determine the correlation between treatment and the components of rice growth and yield, the correlation used is with the Product Moment correlation coefficient. The experimental results showed: (1) The combination of Bioslurry and planting distance affected the number of saplings, root volume, plant growth rate aged 15 HST-25 HST, tuber diameter, fresh tuber weight per clump, dry tuber weight per clump, and dry tuber weight per plot, (2) The highest dry tuber weight per plot of 3.74 kg per plot or equivalent to 9.972 tons / ha (land efficiency 80%) was obtained in the combination of E treatment (bioslurry 50 ml / liter and planting distance 20cm x 15cm), and (3) There was a marked correlation between the number of leaves at 25 HST and 35 HST and the number of saplings in all observation periods with dry tuber weights per plot